KEBIJAKAN PENGELOLAAN ZAKAT DI KABUPATEN SIAK TAHUN 2013-2014 - Puteri, Eka Maya; Marta, Auradian (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
The research present describe the policy of zakat managerial in Siak Regency in 2013-2014. Zakat as a islam basic of rules for every moslem that have to pay and to a people that cannot to complete their life. Zakat managerial are have managing by National Amil Zakat Agency Siak Regency that based on Regulation of District Number 6 in 2013 about the zakat managerial and period of 2013-2014 zakat managerial in Siak Regency has a positive trend and has increase of zakat nominal from payer of zakat.The research use the methode are qualitative methodes that analyze problem research by describe the subject and object conditions based on real fact. This research use location in Siak Regency and researcher collect data from books, government regulation, jurnal, mass media, website and deep interview with informan likes Head of National Amil Zakat Agency of Riau Province, National Amil Zakat Agency of Siak Regency and zakat payer in Siak Regency.The conclution of this research are policy of zakat managerial in Siak Regency have done by some steps from zakat socialization, create a collect zakat unit in every district in Siak Regency and some factors that cause are distribution of zakat, limit of human resources in National Amil Zakat Agency in Siak Regency, communication and coordination of staff National Amil Zakat, disposition of staff and controlling in zakat managerial by National Amil Zakat Nasional Agency in Siak Regency.Keywords: policy, manage, zakat.